Measurement of chromatic dispersion of microstructure optical fibers using interferometric method - Peterka, P.; Kanka, J.; Honzatko, P.; Kacik, D. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
We present a modification of the interferometric method for the measurement of optical fiber chromatic dispersion using an easily aligned, almost all-fiber Michelson interferometer. Particular issues of the microstructure fiber characterization are discussed. Accuracy of the method is validated by comparing the chromatic dispersion measurement of the standard single-mode fiber with results obtained using the phase-shift method.
Optica Applicata, Vol. 38, 2008, nr 2, s. 295-303
Keywords: optyka; chromatic dispersion; optical fiber measurements; microstructure optical fibers